Hard Form of Knowledge Management and Organizational Commitment: A Study on an Organization in the Hospitality Industry - Olufade, Olamide (2018)
To cope with the continuous change in environment, as well as being able to survive in the competitive business environment, nowadays, organizations are seeking several strategies to maintain competitive edge. Survival and success is dependent on how an organization is able to adjust to these changes and also being able to apply knowledge and skills of its employees. Knowledge management has become a vital tool for organizations who are in a competitive industry. The hospitality industry is no different from others in terms of competition, where customers’ needs are ever changing and also places a demand on organizations to maintain quality while satisfying demands. In this same industry, organizations have begun to implement hard form of knowledge management, using software and other electronic platforms in training its employees, despite this being an innovative strategy, they must also take into consideration their most important asset, that is, its employees, whether or not they remain committed. As there are several literatures on knowledge management, but little focuses on the hospitality industry, this research work contributes to the knowledge management literature gap, by studying the effect of hard form of knowledge management on organizational commitment in the hospitality industry, with 40 employees of an organization as participants of this research. The data collected is further analyzed using a statistical tool, SPSS. The Pearson’s correlation coefficient helps to determine the relationship between hard form of knowledge management and organizational commitment. Regression analysis is done on hard form of knowledge management and the sub-variables of organizational commitment in this research work (affective commitment, normative commitment, and continuance commitment).